Potenciālās aprūpes problēmas pacientēm ar krūts vēzi ķīmijterapijas laikā - Kočanova, Janīna (Latvijas Universitāte, 2008)
Pacientēm, kas saņem ķīmijterapiju, ir nepietiekoša informācija par ķīmijterapiju, izglītošanas trūkums par aprūpi pacientēm saprotamā veidā. Darba mērķis ir precizēt aprūpes problēmas pacientēm ar krūts vēzi, kuras saņem ķīmijterapiju. Izmantota kvantitatīvā pētniecības metode. Pētījuma rezultāti atspoguļo, ka pacientu izglītošana, informēšana un tiešais kontakts ir labas pacientu aprūpes pamats. Atslēgvārdi: krūts vēzis, ķīmijterapija, blaknes, aprūpe.

For the patients receiving chemotherapy lack of information about the treatment as well as education concerning cancer care in a way understandable for patients is common. The aim of the work is to emphasize the problems of care for patients with breast cancer receiving chemotherapy, group them in a systemic way in order to provide cancer care. The quantitive method of reserch is used. The resilts of reserch reveal the basic of good cancer care being patient education, information and direct contact. Key words: breast cancer, chemotherapy, side effects, cancer care.
Potential care problems in patients with breast cancer during chemotherapy
Keywords: Medicīna